Case study on genetic algorithm application for solving timetabling problem - 382244 Somchai Enoi (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik Mekatronik)) - Universiti Teknologi Malaysia, 2004